ANALISIS MISKONSEPSI KIMIA SISWA SMA NEGERI 7 KENDARI DALAM MEMAHAMI MATERI TERMOKIMIA - Sri Wulandari; Rustam Musta; Nada Shofa (STKIP Subang, 2026)
This study aims to analyze the level of student misconceptions and identify the factors causing these misconceptions regarding the topic of thermochemistry students at SMA Negeri 7 Kendari. This descriptive study employed a quantitative approach, involving 32 students from class XI Merdeka 5, selected via purposive sampling. The research instruments consisted of a 25-item two-tier multiple-choice diagnostic test, a questionnaire on the causes of misconceptions, and interviews. Data were analyzed descriptively using percentages. The results indicate an average student learning outcome score of 57.38, with the majority of students failing to meet the Learning Objective Achievement Criteria. Diagnostic test results revealed the following average distribution: 14.00% understood the concepts, 40.20% held misconceptions, 15.27% guessed, and 10.47% did not understand the concepts. The highest rates of misconception were found regarding the indicators of enthalpy change properties and bond energy (45.00% each), while the lowest rate was associated with the system and surroundings indicator (23.75%). Questionnaire analysis showed that the causes of misconceptions stemmed from internal factors specifically cognitive aspects (55%), learning interest (60.31%), and learning motivation (61.25%) as well as external factors, including school-related elements (61%) and environmental factors (54.45%). In conclusion, the level of student misconception regarding thermochemistry falls into the moderate category and is influenced by both internal and external factors.